Exceptional widespread, life threatening lung metastasis in stage IA ovarian endometrioid carcinoma: A case report - Shuo-Mei Hung; Jen-Ruei Chen (Elsevier, 2022)
Objective: Low-risk, early stage, ovarian endometrioid carcinoma seems to have little chance to recur in clinical practice. Such a patient developed widespread, life-threatening pulmonary metastases is also extreme rare and is worthy to be reported. Case report: A 53-year-old female, who was diagnosed to have stage IA, grade 2, ovarian endometrioid carcinoma, developed a life threatening widespread lung metastasis in 2 years after primary surgery. She received salvage systemic chemotherapy with paclitaxel plus carboplatin. Bevacizumab was added after occurrence of paroxysmal supraventricular tachycardia during chemotherapy. The patient had clinical improvement and radiological stable after systemic therapy. Conclusion: Our case report enhances the aggressive post-operative surveillance including chest field would still be recommended even in the low-risk patients. To detect distant metastases earlier probably has higher chance of cure by systemic therapy.